(untitled) (IAHS Medical Journal, 2023)
Background: Virtual dentistry practices, when implemented correctly, reduce the burden on healthcare systems by preventing COVID-19 and asymptomatic carriers from infecting healthcare professionals and high-risk employees. This study was carried out to evaluate the perception and state of teledentistry practices among the dentists during COVID-19 pandemic. Materials and methods: A descriptive cross-sectional study was conducted among 218 dentists through a semistructured questionnaire to evaluate the state of teledentistry practices among 6 dental colleges and hospitals in Dhaka City. Results: Most of the dentists (87.2%) mentioned that teledentistry practice increased during COVID-19 pandemic and it has reduced the spread of infection. Majority recommended teledentistry is a good tool for oral hygiene instruction (72.5%) but couldn’t provide accurate diagnosis (73.9%). One fourth of the respondents (26.1%) prescribed medicine virtually and others prefer providing health education and counseling only. There are some barriers during practicing teledentistry such as poor audio or audio-video quality, expensive set-up, accurate diagnosis provision and difficulty to use software. Conclusion: Teledentistry isn’t intended to replace traditional methods of treatment that involve patient examination, but rather to provide a new way to practice healthcare. Dentists should be encouraged to practice virtual health education tool which may lower the cost burden, overcrowding and spread of COVID-19. IAHS Medical Journal Vol 5(2), Dec 2022; 25-28